Wages and working conditions in the context of digitalization - Rysty, Sabirova; Zhanargul, Suleimenova; Ainur, Tazhidenova; Sharbat, Bissaliyeva; Zhanat, Yerniyazova (International Journal of Innovative Research and Scientific Studies, 2025)
Artificial intelligence is transforming our way of life and work, and its impact on the future of work is the subject of numerous discussions. The development of AI technologies is reshaping the labor market and the skills that employers value in their employees. Today, the digital transformation of the economy has become a major trend that provides significant support for the sustainable development of our economy, improves quality and efficiency, and has a profound impact on employment. The article examines the impact of workplace digitalization on pay equity and working conditions. The study revealed that improving the quality of workplace digitalization creates new opportunities and presents new challenges for the labor market. Enhancing the digitalization process of workplaces has led to an increase in average wages. The level of wages provides vulnerable groups such as women, the elderly, and individuals with low levels of education with the opportunity to earn equal pay and has a positive impact on the protection of fundamental rights and interests, greater flexibility in employment, and increased job satisfaction. On the other hand, workplace digitalization also exacerbates wage inequality. Self-employed workers face heavier workloads and longer overtime hours. Voluntary, unpaid overtime work undermines the rights and interests of workers.